PELATIHAN PENANGANAN ANAK TERSEDAK PADA KADER POSYANDU DIWILAYAH KERJA PUSKESMAS KAMAL - Heni Ekawati; Ulva Noviana; M. Hasinuddin (STIKES NGUDIA HUSADA MADURA, 2019)
Choking is an emergency condition that must be treated quickly. If left for too long without handling the body can experience a lack of oxygen (hypoxia) and can lead to death (Kalcare, 2014). Based on research conducted by Rovin (2013), there were 12,400 cases of children under 14 years of age from 2001 to 2009 who came to the ER because of choking, found 34 were taken to the ER (emergency room) and 57 children died every year because they could not. adequate aid when choking. Based on a survey conducted at Posyandu RW 6 in the Puskesmas Kamal area, through interviews with parents that have been conducted, it was found that many parents still do not know about first aid for choking children and its prevention. The method used to carry out community service is coordination with the posyandu coordinator as well as the appointment of cadres and determining the schedule of activities for providing material on the implementation of training in handling choking children. Then a cadre here will tell parents how to handle a choking child. In this training activity, there were 8 cadres in the Posyandu RW 6 area and cadres in the posyandu in the Kamal Puskesmas working area. During the activity, the cadres were very enthusiastic about the material presented. The cadres were also evaluated before and after being given material on the handling of choking in children. Apperception activities were carried out, namely the exploration of cadres' knowledge regarding the material. After evaluating the results, the cadres understood how to treat choking children